The concept of happiness according to Ibn Hazm and Martin Seligman - Umam, Yaul; Noor, Rifqi Nazahah; Soleh, Achmad Khudori (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2025)
The purpose of this article is to describe the happiness of Ibn Hazm and Martin Seligman. Ibn Hazm was a Muslim philosopher, while Seligman was a modern psychologist and secularist. These different concepts of happiness are interesting to study because they represent two major paradigms: Islamic ethical spiritualism and modern positive psychology, which are rarely directly compared. This comparison offers novelty by opening up a more holistic perspective on happiness. The method used is qualitative research with a comparative approach and narrative review. The primary sources used are